Perivascular sirolimus-delivery system - Filová, Elena; Pařízek, Martin; Olšovská, Jana; Kameník, Zdeněk; Brynda, Eduard; Riedel, Tomáš; Vandrovcová, Marta; Lisá, Věra; Machová, Luďka; Skalský, Ivo; Szarszoi, Ondrej; Suchý, Tomáš; et al. (International journal of pharmaceutics, 2011)
Autologous vein grafts are often used for treating damaged vessels, e.g. arteriovenous fistulas or arterial bypass conduits. Veins have a different histological structure from arteries, which often leads to intimal hyperplasia and graft restenosis. The aim of this study was to develop a perivascular sirolimus-delivery system that would release the antiproliferative drug sirolimus in a controlled manner. Polyester Mesh I was coated with purasorb, i.e. a copolymer of L-lactide and ɛ-caprolactone, with dissolved sirolimus; Mesh II was coated with two copolymer layers; the layer with dissolved sirolimus was overlaid with pure purasorb. This arrangement allowed sirolimus to be released for 6 and 4 weeks, for Mesh I and Mesh II, respectively. Mesh II released sirolimus more homogeneously, without the initial burst effect during the first week. However, the cumulative release curve was steeper at later time points than the curve for Mesh I. Both meshes inhibited proliferation of rat vascular smooth muscle cells during 14-day culture in vitro and preserved excellent cell viability. Newly developed sirolimus-releasing perivascular meshes are promising devices for preventing autologous graft restenosis.
Keywords: molekulová hmotnost; Animals; Chromatography, High Pressure Liquid; potkani Wistar; rozpustnost; vysokoúčinná kapalinová chromatografie; Surface Properties; zvířata; proliferace buněk; farmaceutická chemie; kinetika; sirolimus; nosiče léků; Cardiovascular Agents; stabilita léku; Coated Materials, Biocompatible; Myocytes, Smooth Muscle; Rats; Microscopy, Electron, Scanning; Cells, Cultured; Sirolimus; farmaceutická technologie; Drug Compounding; Male; Rats, Wistar; kardiovaskulární látky; léky s prodlouženým účinkem; biokompatibilní potahované materiály; polyestery; Delayed-Action Preparations; Kinetics; Molecular Weight; Solubility; Drug Carriers; myocyty hladké svaloviny; Polyesters; krysa rodu Rattus; Chemistry, Pharmaceutical; Cell Proliferation; Technology, Pharmaceutical; Drug Stability; Graft Occlusion, Vascular; příprava léků; povrchové vlastnosti; okluze cévního štěpu; kultivované buňky; svaly hladké cévní; mužské pohlaví; Muscle, Smooth, Vascular; mikroskopie elektronová rastrovací